Prenatal traffic‐related air pollution exposures, cord blood adipokines and infant weight. Issue 6 (3rd November 2017) - Alderete, T. L.; Song, A. Y.; Bastain, T.; Habre, R.; Toledo‐Corral, C. M.; Salam, M. T.; Lurmann, F.; Gilliland, F. D.; Breton, C. V.
Summary: Objective: Studies suggest that prenatal exposure to traffic‐related air pollution (TRAP) may contribute to childhood obesity. While exact mechanisms for this association are unknown, circulating adipokines are hypothesized to contribute to early‐life weight gain. Methods: The Maternal and Child Health Study birth cohort included 136 women from the Los Angeles County + University of Southern California Medical Center. This study estimated prenatal residential TRAP exposure and used linear regression analysis to examine associations between adipokines with TRAP exposure and infant weight change (birth to 6 months). Results: A one standard deviation (1‐SD: 2 ppb) increase in prenatal non‐freeway nitrogen oxides was associated with 33% ( P = 0.01) higher leptin and 9% higher high molecular weight adiponectin levels ( P = 0.07) in cord blood. Leptin levels were 71% higher in mothers who lived <75 m than those living >300 m from major roadways ( P = 0.03). A 1‐SD (10 ng mL −1 ) increase in leptin was associated with a significant increase in infant weight change in female infants (0.62 kg, P = 0.02) but not male infants (0.11 kg, P = 0.48). Conclusions: Higher TRAP exposures were associated with higher cord blood levels of leptin and high molecular weight adiponectin. These adipokines were associated with increased infant weight change in female infants, which may have implications for future obesity risk.